A case report on gonadal dysgenesis caused by a rare NR5A1-associated contiguous gene deletion: a diagnostic challenge - G., Shiny Nivya; K., Vidhya Jayashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Disorders of sexual development (DSD) encompass a diverse group of congenital conditions characterised by atypical development of chromosomal, gonadal, or anatomical sex. Among these, NR5A1 mutations represent an important and heterogeneous cause of 46, XY DSD, often exhibiting wide phenotypic variability with limited genotype–phenotype correlation. Early incorporation of genetic testing is therefore pivotal, particularly when gonadal dysgenesis is suspected. We present a 19-year-old individual, raised as female, who presented with primary amenorrhoea and underdeveloped secondary sexual characteristics. Endocrine testing showed hypergonadotropic hypogonadism, and karyotyping identified a genotype of 46, XY. Genetic testing revealed a contiguous deletion involving the NR5A1 gene, consistent with severe gonadal dysgenesis. Pelvic magnetic resonance imaging showed the presence of an infantile uterus, but, on diagnostic laparoscopy, complete Müllerian agenesis was discovered. Bilateral gonadectomy showed dysgenetic testes without signs of malignancy. This case highlights the diagnostic complexity of NR5A1-related DSD, the potential discordance between imaging and operative findings, and the importance of a multidisciplinary approach to ensure accurate diagnosis and appropriate management.